HUBUNGAN ASUHAN KEPERAWATAN DENGAN TINGKAT KEPUASAN PASIEN THYPOID FEVER DI UPT.PUSKESMAS PARAGAAN KABUPATEN SUMENEP - Utami, Utami; Hayadi, Moh. Lukmanur (JURNAL NERS LENTERA, 2018)
Introduction: System of health care services is changing rapidly according to changing needs and expectations of the public about health care. People are increasingly demanding better health care with respect to an increasing public knowledge of health care. Nursing process represents a system of nursing care service plan consisting of four stages of assessment, planning, Implementation and evaluation. The purpose of the present study was to determine relationship of nursing care and satisfaction levels of patients with typhoid fever in Public Health Center of Pragaan, Sumenep. Method: The present study was of analytic observational and cross-sectional. Population was 50 respondents with a sample of 45 subjects. Data was collected by means of questionnaires and analyzed by chi-square test. Result: Indicated that 51.1% (23 patients) stated that nursing care provided by nurses for patients with typhoid fever was fairly high. With regard to satisfaction levels of patients with typhoid fever, 75.6% (34 patients) indicated satisfaction with nursing care provided by nurses. It meant that there was a relationship of nursing care and satisfaction levels of patients with typhoid fever. Discussion: Nurses were expected to continuously improve care quality that included nursing care in order to improve satisfaction of patients with typhoid fever.